A comparative assessment of the impact of corporate social responsibility on Islamic Bank Bangladesh Limited - Hossain, MD Arman (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2021.